Qué explica el precio del vino? Análisis hedónico del mercado de alta calidad - Ignacio Benito Amaro; Gustavo Ferro (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
– We determine a relationship between high quality wines and its drivers. We answer the questions: What variables explain high-quality wine prices? How do certain factors (highly, slightly or scarcely) under control of the suppliers, influence prices? To respond, we build a database with thirteen years of the best 100 wines annually ranked in Wine Spectator magazine. With the database we estimate a hedonic price regression. We also identify wineries, origins and a country whose wines are "overvalued" or "undervalued" with respect to model's predictions.
Keywords: D12; C20; L66; 330; wine; hedonic prices